Predicted Chance That Global Warming Will Temporarily Exceed 1.5 °C. Issue 21 (4th November 2018) - Smith, D. M.; Scaife, A. A.; Hawkins, E.; Bilbao, R.; Boer, G. J.; Caian, M.; Caron, L.‐P.; Danabasoglu, G.; Delworth, T.; Doblas‐Reyes, F. J.; Doescher, R.; Dunstone, N. J.; et al.
Abstract: The Paris Agreement calls for efforts to limit anthropogenic global warming to less than 1.5 °C above preindustrial levels. However, natural internal variability may exacerbate anthropogenic warming to produce temporary excursions above 1.5 °C. Such excursions would not necessarily exceed the Paris Agreement, but would provide a warning that the threshold is being approached. Here we develop a new capability to predict the probability that global temperature will exceed 1.5 °C above preindustrial levels in the coming 5 years. For the period 2017 to 2021 we predict a 38% and 10% chance, respectively, of monthly or yearly temperatures exceeding 1.5 °C, with virtually no chance of the 5‐year mean being above the threshold. Our forecasts will be updated annually to provide policy makers with advanced warning of the evolving probability and duration of future warming events. Plain Language Summary: The Paris Agreement calls for efforts to limit human‐induced global warming to less than 1.5 °C above preindustrial levels. Observations of global mean temperature contain both human‐induced temperature change and superimposed natural variability. Natural variability may temporarily add to the underlying human‐induced warming, leading to observed temperatures that are higher than 1.5 °C for short‐term periods. This would not necessarily exceed the Paris agreement, which is usually interpreted to refer to long‐term averages, but would give an important indication that the threshold is being approached. If exceedance occurs, policy makers will require guidance regarding how long temperatures will remain above the threshold. Here we develop a new capability to predict the likelihood that global temperature will exceed 1.5 °C above preindustrial levels in the coming 5 years. We use decadal climate predictions that are regularly produced by several international climate prediction centers. Importantly, these predictions take into account the observed present day conditions since this is essential to predict the evolution of natural variability. For the period 2017 to 2021 we predict a 38% and 10% chance, respectively, of monthly or yearly temperatures exceeding 1.5 °C, with virtually no chance of the 5‐year mean being above the threshold. We will update our forecasts every year to provide policy makers with advanced warning of the evolving probability and duration of future warming events. Key Points: Early temporary excursions above 1.5 °C would provide a warning that one of the Paris Agreement thresholds is being approached Initialized climate predictions indicate a 38% (10%) chance of at least 1 month (year) exceeding 1.5 °C in the 5 year period 2017‐2021 Five‐year mean temperatures above 1.5 °C are extremely unlikely in this period